Mapping, Modeling, and Estimating Tree Measurements of Urban Tree Canopy Structure Using Terrestrial LiDAR Scanning. (2nd April 2016) - Jones, Tyler; Marzen, Luke; Chappelka, Art
ABSTRACT: The major objective of this study was to estimate standard metrics and estimate foliar measurements (crown volume and leaf area) and standing biomass of open grown Nuttall oak ( Quercus texana ). Specifically the study used terrestrial light distance and ranging (LiDAR) for initial mapping and subsequent modeling of these popular urban trees. Field data were collected using a Leica C-10 high-definition scanner with registration and modeling conducted using a combination of Leica's Cyclone and the LANDRIVON 3DReshaper software suite. Destructive sampling of three Nuttall oaks was then performed to obtain metrics for comparison to the models generated using the software. Several modeling methods were attempted, each with varying degrees of complexity to synthesize a workflow that would accurately reflect the measurements seen during destructive sampling. Promising results suggest there could be a correlation using these methods, although further testing is needed.